Neuromuscular Fatigue and Physiological Responses After Five Dynamic Squat Exercise Protocols. Issue 4 (April 2016) - Raeder, Christian; Wiewelhove, Thimo; Westphal-Martinez, Marc P.; Fernandez-Fernandez, Jaime; de Paula Simola, Rauno A.; Kellmann, Michael; Meyer, Tim; Pfeiffer, Mark; Ferrauti, Alexander
Abstract : Abstract: Raeder, C, Wiewelhove, T, Westphal-Martinez, MP, Fernandez-Fernandez, J, de Paula Simola, RÁ, Kellmann, M, Meyer, T, Pfeiffer, M, and Ferrauti, A. Neuromuscular fatigue and physiological responses after five dynamic squat exercise protocols. J Strength Cond Res 30(4): 953–965, 2016—This aimed to analyze neuromuscular, physiological and perceptual responses to a single bout of 5 different dynamic squat exercise protocols. In a randomized and counterbalanced order, 15 male resistance-trained athletes (mean ± SD ; age: 23.1 ± 1.9 years, body mass: 77.4 ± 8.0 kg) completed traditional multiple sets (MS: 4 × 6, 85% 1 repetition maximum [RM]), drop sets (DS: 1 × 6, 85% 1RM + 3 drop sets), eccentric overload (EO: 4 × 6, 70% 1RM concentric, 100% 1RM eccentric), flywheel YoYo squat (FW: 4 × 6, all-out), and a plyometric jump protocol (PJ: 4 × 15, all-out). Blood lactate (La), ratings of perceived exertion (RPE), counter movement jump height (CMJ), multiple rebound jump (MRJ) performance, maximal voluntary isometric contraction force, serum creatine kinase (CK) and delayed onset muscle soreness were measured. Immediately post exercise, La was significantly ( p < 0.001) higher in FW (mean ± 95% confidence limit; 12.2 ± 0.9 mmol·L −1 ) and lower in PJ (3.0 ± 0.8 mmol·L −1 ) compared with MS (7.7 ± 1.5 mmol·L −1 ), DS (8.5 ± 0.6 mmol·L −1 ), and EO (8.2 ± 1.6 mmol·L −1 ), accompanied by similar RPE responses. Neuromuscular performance (CMJ, MRJ) significantly remained decreased ( p < 0.001) from 0.5 to 48 hours post exercise in all protocols. There was a significant time × protocol interaction ( p ⩽ 0.05) in MRJ with a significant lower performance in DS, EO, and FW compared with PJ (0.5 hours post exercise), and in EO compared with all other protocols (24 hours post exercise). A significant main time effect with peak values 24 hours post exercise was observed in CK serum concentrations ( p < 0.001), but there was no time × protocol interaction. In conclusion, (a) metabolic and perceptual demands were higher in FW and EO compared with MS, DS and PJ, (b) neuromuscular fatigue was consistent up to 48 hours post exercise in all protocols, and (c) EO induced the greatest neuromuscular fatigue.